1979
DOI: 10.1055/s-0028-1092675
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Leucine-lnduced Insulin Secretion by Somatostatin Antiserum Pretreatment

Abstract: Insulin secretion induced by leucine and leucine plus glucose from rat pancreatic islets was enhanced by prior treatment with somatostatin antiserum as compared with normal rabbit serum in vitro. The results provide evidence that somatostatin plays an important role in insulin secretion in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In [S ,201 an increase in insulin release with antisomatostatin serum was also observed but only at a sub-stimulatory or intermediate but not at high glucose concentration. However, the experimental design in [5,20] differed from ours; they preincubated the islets with the antiserum and tested insulin release thereafter without antiserum in the presence of glucose or/and leucine only. Work with precultured rat islets [6] revealed no influence of anti-somatostatin serum on insulin output.…”
Section: Discussionmentioning
confidence: 99%
“…In [S ,201 an increase in insulin release with antisomatostatin serum was also observed but only at a sub-stimulatory or intermediate but not at high glucose concentration. However, the experimental design in [5,20] differed from ours; they preincubated the islets with the antiserum and tested insulin release thereafter without antiserum in the presence of glucose or/and leucine only. Work with precultured rat islets [6] revealed no influence of anti-somatostatin serum on insulin output.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been demonstrated subsequently with very small doses of somatostatin (Lins and Efendic 1979). Studies in vitro have shown that the removal of endogenously released somatostatin by neutralizing antibodies increases insulin release in response to glucose and amino acids (Taniguchi et al 1977;Taniguchi et al 1979). Recent studies in vivo have demonstrated that the removal of circulating somatostatin leads to an increase in postprandial but not basal insulin secretion, suggesting the possibility of an endocrine interaction between insulin and somatostatin (Schusdziarra et al 1980).…”
Section: Insulin -Somatostatin Interrelationshipmentioning
confidence: 99%
“…These data provide evidence that pancreatic somatostatin is a mediator of the suppression of glucagon during hyperglycemia. Diabetes 36:592-96, 1987 I t has been proposed that somatostatin from the 8-cells of the pancreatic islet (1) tonically inhibits pancreatic glucagon and insulin secretion by a paracrine mechanism (1)(2)(3)(4)(5)(6)(7)(8). This hypothesis is based partly on the known inhibitory effect of pharmacologic doses of somatostatin on insulin and glucagon secretion in all species (9)(10)(11) and the anatomical position of the 8-cells between the outer mantle of a-cells and an inner core of p-cells in the rat islet (1,7,8).…”
mentioning
confidence: 99%